Strategi Diseminasi Produk dan Respons Masyarakat terhadap Inovasi Sabun dan Handsanitizer Berbahan Mangrove di Kampung Buti, Merauke, Papua Selatan - Sajriawati Sajriawati; Sunarni Sunarni; Nurliah Nurliah (Lembaga Pengembangan Kinerja Dosen, 2025)
Environmental sanitation and hygiene are crucial for preventing skin and infectious diseases, especially in coastal areas. This has led to increased interest in developing environmentally friendly natural alternatives. Mangrove leaves have been studied for their significant antibacterial properties due to bioactive compounds such as saponins and flavonoids. Buti Village is one of the coastal villages with mangrove potential. Although several previous studies have confirmed the technical feasibility of mangrove-based products, there is limited literature on empirical dissemination strategies and community responses, particularly in the 3T (Frontier, Outermost, and Disadvantaged) areas. This study addresses this gap by evaluating dissemination strategies and community responses to innovative mangrove-based soap and hand sanitizer products in Buti Village, Merauke, South Papua. Using a quantitative descriptive approach supported by qualitative research, the study involved a purposive sample of 40 local residents. The dissemination strategy included participatory training, product demonstrations, and educational brochures. Findings showed a high level of acceptance, with 86% of respondents accepting the product, and a significant level of self-reliance, with 81% of participants able to independently produce soap and hand sanitizer products. This demonstrates that a participatory, educational, and locally-based approach is effective in building knowledge and positive attitudes toward environmentally friendly innovations. This research demonstrates that these innovations have significant potential to become sustainable community-based small businesses that can strengthen the local economy while promoting mangrove conservation.